EFEITOS ESQUELÉTICOS DA TRAÇÃO REVERSA DA MAXILA UTILIZANDO TOMOGRAFIA COMPUTADORIZADA - Kim, Jin Hyun (2011)
This study evaluated the skeletal effects of maxillary protraction using 2D images (lateral radiograph) generated from the cone beam CT (3D images). The sample consisted of 20 children (15 females and 5 males), aged 5,6 -10,7 years who had malocclusion Class III malocclusion. CT was performed before treatment (T1) and after treatment (T2). The treatment was performed by maxillary protraction using the Hyrax expansion appliance associated with individualized face mask with the force of 600 to 800g each side for 14 hours a day. The correction of canine relationship in Class I or Class II in their overcorrection was obtained after 4-7 months of treatment. To check the systematic error and random test was used for paired "t" and the formula of Dahlberg, respectively. The test paired "t" (p <0.05) showed a significant difference between the cephalometric measurements obtained in T1 and T2. In the maxilla there were increases in SNA 2.2°, Nperp A 1.47mm and Co-A 2.58mm. In the mandible, SNB decreased by -0.54° and P-Nperp, -1.45mm, while Co-Gn increased 1.04mm. There was improvement in maxillomandibular relationship ANB 2.74° and Wits 4.23mm. Variables GoGn.SN, Gn.SN, FH.Md, Mx.Md and AFAI demonstrating that there was an increased rotation of the mandible in a clockwise direction. The palatal plane rotated in a counterclockwise direction. It can be concluded that the treatment ofmaxillary protraction in early age has promoted an improvement in maxillomandibular relationship due to a shift of the jaw forward and a displacement of the mandible down and back.